Juridical impact of urf on family law: an applied juristic framework for local fiqh - Haneef, Sayed Sikandar Shah; Abdul Razak, Mohd Abbas; Laluddin, Hayatullah (Contemporary Fiqh Research Unit (CFRU) &Islamic Book Trust, 2021)
This chapter offers an exposition of compact and precise juristic attempts in assimilating local norms and customs into their reading in the process of applying both specific and general principles of revealed laws into day-to-day matters of family affairs. The lessons drawn from this study can be of paramount significance to the contemporary discourse on family fiqh in Malaysia.